2013
DOI: 10.4185/rlcs-2013-992en
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal impact and cognitive channelling of immigration stereotypes through the news

Abstract: Introduction: Based on research on the framing effect and research on the treatment of immigration, the processes of reception and impact of news about crime are analyzed. Method: We conducted two experimental investigations in which participants were exposed to a news story and later filled in a questionnaire with self-report scales. Two independent variables were manipulated: the mention of protagonists' national/ geographic origin in the news story and the involvement with the topic. Results: The study indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
1
13
0
3
Order By: Relevance
“…Given that these portrayals of immigrants are overwhelmingly negatively biased, exposure to these political posters is likely to perpetuate stereotypic attitudes toward foreigners. Although numerous studies support the idea that negatively biased news coverage enhances negative attitudes toward ethnic minorities (e.g., Igartua, 2013), the effects of right-wing populist political posters on people's attitudes toward immigrants and ethnic minorities have so far not sufficiently been studied.…”
Section: Right-wing Populist Advertisingmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that these portrayals of immigrants are overwhelmingly negatively biased, exposure to these political posters is likely to perpetuate stereotypic attitudes toward foreigners. Although numerous studies support the idea that negatively biased news coverage enhances negative attitudes toward ethnic minorities (e.g., Igartua, 2013), the effects of right-wing populist political posters on people's attitudes toward immigrants and ethnic minorities have so far not sufficiently been studied.…”
Section: Right-wing Populist Advertisingmentioning
confidence: 99%
“…Although these anti-immigrant populist poster ads may have damaging implications for democracy and processes of integration, little research has been done on their effects. In most research available to date, scholars examined the news coverage of minorities as an important cause of negative attitudes (e.g., Boomgaarden & de Vreese, 2007;Boomgaarden & Vliegenthart, 2007;Igartua, 2013;Igartua & Cheng, 2009;Igartua, Moral-Toranzo, & Fernández, 2011;Schemer, 2012Schemer, , 2014. For instance, news content analysis has revealed that immigrants are mostly depicted in a negative context and are associated with negative issues, such as crime or terrorism (Dixon & Linz, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the practical implications of the results of our study, and in relation to the development of campaigns for raising awareness of gender violence, it would be advisable to work with narratives in which the nationality of the protagonist is not indicated (or shown indirectly), as this can condition the effectiveness of the message (see, Igartua, 2013, where experimental evidence is provided on the attitudinal impact of crime news that alludes to the nationality of offenders). Campaigns designed to raise awareness of gender violence that feature protagonists who are immigrants (as a stigmatized out-group) could reinforce stereotypes about the link between immigration and gender violence, and thus have a pernicious effect, instead of contributing to the eradication of gender violence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As an independent variable, frame is understood as a part of accentuated news text, which is capable of affecting the reception process and has an effect on the users. This is the part that is often studied in relation to the framing effect (Igartua, 2013;Borah, 2011), including this article. News framing may influence a person's mind (in their cognitive response) and it may influence their perceptions and beliefs concerning issues discussed within a particular news, which ultimately may lead to changes in behavior and belief.…”
Section: Theoretical Framework 1 Framing Conceptmentioning
confidence: 99%